Engineering of L-Plastin Peptide-Loaded Biodegradable Nanoparticles for Sustained Delivery and Suppression of Osteoclast Function In Vitro - Sunipa Majumdar; Aniket S. Wadajkar; Hanan Aljohani; Mark A. Reynolds; Anthony J. Kim; Meenakshi Chellaiah (International Journal of Cell Biology)
We have recently demonstrated that a small molecular weight amino-terminal peptide of L-plastin (10 amino acids; “MARGSVSDEE”) suppressed the phosphorylation of endogenous L-plastin. Therefore, the formation of nascent sealing zones (NSZs) and bone resorption are reduced. The aim of this study was to develop a biodegradable and biocompatible PLGA nanocarrier that could be loaded with the L-plastin peptide of interest and determine the efficacy in vitro in osteoclast cultures. L-plastin MARGSVSDEE (P1) and scrambled control (P3) peptide-loaded PLGA-PEG nanoparticles (NP1 and NP3, respectively) were synthesized by double emulsion technique. The biological effect of nanoparticles on osteoclasts was evaluated by immunoprecipitation, immunoblotting, rhodamine-phalloidin staining of actin filaments, and pit forming assays. Physical characterization of well-dispersed NP1 and NP3 demonstrated ~130-150 nm size, < 0.07 polydispersity index, ~-3 mV ζ-potential, and a sustained release of the peptide for three weeks. Biological characterization in osteoclast cultures demonstrated the following: NP1 significantly reduced (a) endogenous L-plastin phosphorylation; (b) formation of NSZs and sealing rings; (c) resorption. However, the assembly of podosomes which are critical for cell adhesion was not affected. L-plastin peptide-loaded PLGA-PEG nanocarriers have promising potential for the treatment of diseases associated with bone loss. Future studies will use this sustained release of peptide strategy to systematically suppress osteoclast bone resorption activity in vivo in mouse models demonstrating bone loss.